El rito aymara del "despacho" - Mayorga, Sylvia (1976)
In the present work we intend to document an Aymara ritual ceremony, called "despacho". For this purpose we will proceed first to present the corresponding ethnography and then we will analyze the symbols and the ritual ceremony, using the following terms as synonyms: "table", "payment", "offering", "office", "alcansu", and "pagapu". ". It is also necessary to clarify that we have used a series of Kechua-Aymara terms whose meanings we do not explain because we understand that they are widely known and used in the anthropological literature of the Andean area.